GENETIC DIVERSITY IN ADVANCED GENERATION OF VEGETABLE PEA (Pisum sativum L.) (Bangladesh Journal of Plant Breeding and Genetics, 2015)
Twenty five advanced lines among them twelve lines obtained from the cross between Edible Podded Pea and IPSA Motorsuty-1, nine obtained from the cross between Local White and IPSA Motorsuty-3 and five parental lines were included to measure genetic diversity. The field experiment was conducted at the research farm, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh. Analysis of variance showed significant differences among the genotypes for all characters. Multivariate analysis based 14 agronomic characters indicated that the 26 genotypes fell into five distant clusters. Fifty percent germination was found to be contributed maximum towards the total divergence. The inter cluster (D2 values) distance was maximum between cluster I and cluster II and intra-cluster distance was in cluster III. Cluster V comprising five genotypes, namely, G11, G14, G21, G22, G25 and scored first position for 50% germination, pod per plant, 100 green seed weight and seed yield per plant (6.02). Genotypes belonging to the cluster I, II and V having greater inter cluster distance and higher cluster means for various characters could be recommended for inclusion in future breeding program as they are expected to produce good segregates.